PENGARUH KECERDASAN EMOSIONAL, KECERDASAN SPRITUAL DAN PERILAKU BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTASI (Studi Empiris Pada Mahasiswa Akuntansi Universitas Islam Malang, Universitas Negeri Malang, dan Universitas Islam Negeri Maulana Malik Ibrahim Malang) - Moh. Tarmidzi Kusuma Halim; Noor Shodiq Askandar; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This research was conducted with the aim of knowing the effect of emotional intelligence, spiritual intelligence, and learning behavior on the level of understanding of accounting either partially or simultaneously. This research is included in a quantitative research approach that focuses on testing hypotheses, collecting data in this study using a questionnaire distributed to students. The population in this study were active students of the Accounting Study Program at the Islamic University of Malang, State University of Malang, and the State Islamic University of Maulana Malik Ibrahim Malang. The number of active accounting students at the Islamic University of Malang was 950, for the number of active accounting students at the State University of Malang was 1000, and for There are 800 students of the State Islamic University of Maulana Malik Ibrahim Malang out of a total population of 2,750 active students. Then for sampling, the slovin. formula is used, the data analysis technique in this study is to use the statistical package for social sciences (SPSS) for windows version 22 program. The results of this study indicate that simultaneously emotional intelligence, spiritual intelligence, and learning behavior have a significant effect on the level of accounting understanding with a significance value (0.000 <0.05), emotional intelligence has no partial effect on the level of accounting understanding with a significant value of 0.667> 0.05, spiritual intelligence has a negative effect on the level of accounting understanding with a significance value of 0.000 <0.05, learning behavior has a positive effect on the level of accounting understanding with a significance value of 0.000> 0.05.Keywords : The Effect of Emotional Intelligence, Spiritual Intelligence and Learning Behavior on Accounting Understanding